The quantification of testicular cells during the postnatal development in two Caviomorph rodents: The guinea pig (Cavia porcellus) and the cutia (Dasyprocta agouti) - Simões, Luciana S.; Sasahara, Tais H. C.; Favaron, Phelipe O.; Marques Júnior, Ricardo; de Oliveira, Moacir F.; Machado, Márcia R. F. [UNESP]; Miglino, Maria Angelica (FapUNIFESP (SciELO), 2017)
The germinative, Sertoli and Leydig cells of two caviomorph rodents (Cavia porcellus and Dasyprocta agouti) were counted as well as the estimation of the total volume of the testis and the total volume of seminiferous tubules and interstitium in prepubertal, pubertal and adult animals. The number of spermatogonia, spermatocytes and spermatids cells increased during the pubertal phase in both rodents, notably the spermatid cells. The spermatocyte and spermatid slightly decreased in the adult of both rodents, but the increment in spermatogonia cells number was seen, mainly in cutias. The number of Sertoli cells increased in pubertal rodents, but in the adult the number reduced. Substantial number of Leydig cells was counted in pubertal and adult guinea pigs. In cutias, the number of Leydig cells increased in pubertal phase and decline in adults. The design-based stereological method has proven to be unbiased and reliable to be applied in reproduction studies.
Keywords: Germinative cells; Hystricomorpha; Reproduction; Stereology